WACANA MANTRA DUKUN BERANAK MELAYU RIAU - Iroy Mahyuni; Sudartomo Macaryus (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to describe (1) Content of mantra, (2) the form of mantra, (3) function, (4) inheritance of mantra Â Melayu Riau. This type of research is qualitative research. The data in this study a lingual unit that forms a spell Melayu Riau. The data used in this study is three, namely Datok Sodah, Nenek Lambiah, and Nenek Terima. The method of providing data in this study using records. Techniques providing data using the tapping technique. The validity of the data by using the extension of participation and persistence observations. Data analysis method used is the method of ethnography. The data analysis was done by using domain analysis. The results showed that (1) Content spell includes stages prenatal, childbirth and postnatal, which rejects interference, testimony, and plea. Tapahan prenatal can be viewed Kato landslide Dead Bedarah, Cus Sibalucus, Si Tampun-Tampun, Sireh Lillah, Eggplant Lillah, Oil Lillah, Dokon foursome, and Petandoan. Stages of the birth process, namely Ring Geligo Sea, Membukak Lawang (Datok Saodah), Membukak Lawang (Grandma Lambiah), Dokon Betujoh, Key Sire Ali, Wada Wadi Maknikam, Tetak Duri Tampong Duri, Officer King Ali, Selusoh carrion, Said Witness, if Dead Son, Birah Black (Datok Saodah), Sibalucus, Membukak Lawang (Grandma Accept), Tawa Stickiness Uri, Selusoh Slaves, Ketigo Chicken, Nature Teberakai, and Sindai Teruno. Sindai postnatal stages uno, Children Anjeng Kuyok Buto, invisibility Rayo, Senengkat, invisibility Chaff, Tiong Gano, Sirejang Anjeng, Birah Black (Grandma Lambiah), Salam Gumi, Hillahi Tegu, Origin Land, and Tawa Param. (2) Form spell, namely poetry, prose and free verse lyrics. (3) Function spells, which accelerates the process of birth, to overcome the difficulties in childbirth, birth overcome distorted, and the safety of women and their babies. (4) Inheritance spells Melayu Riau open to the public.